Antibiotic treatment for intermittent bladder catheterisation with once daily prophylaxis (the AnTIC study): Study protocol for a randomised controlled trial. Issue 1 (December 2016) - Brennand, Catherine; von Wilamowitz-Moellendorff, Alexander; Dunn, Sarah; Wilkinson, Jennifer; Chadwick, Thomas; Ternent, Laura; Oluboyede, Yemi; Wood, Ruth; Walton, Katherine; Fader, Mandy; N'Dow, James; Abdel-Fattah, Mohamed; et al.
Abstract Background Clean intermittent self-catheterisation is an important management option for people who cannot empty their bladder effectively. Recurrent urinary tract infections are common in these patients. Data from recent studies suggest that antibiotic prophylaxis may be beneficial in reducing infection risk, but the effectiveness of this intervention remains uncertain. Methods/design This is a 52-site, patient randomised superiority trial set in routine care comparing an experimental strategy of once daily antibiotic prophylaxis for 12 months against a control strategy of no prophylaxis in people who carry out self-catheterisation and suffer recurrent urinary tract infections. The primary outcome is number of urinary tract infections during a 12-month treatment period. Both groups will otherwise receive usual care including on demand treatment courses of antibiotics for urinary tract infection. Participants and their clinicians will not be blinded to the allocated intervention, but central trial staff managing and analysing trial data will, as far as possible, be unaware of participant allocation. The analysis will follow intention-to-treat principles. Discussion This trial was commissioned and funded by the United Kingdom National Health Service following prioritisation of the research question by the National Institute for Health and Care Excellence. Trial registration ISRCTN67145101 EUDRACT2013-002556-32. Registered on 25 October 2013.